If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 2b = -16 Combine like terms: 2b + 2b = 4b 4b = -16 Solving 4b = -16 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '4'. b = -4 Simplifying b = -4
| 8-(1/2)y=-6 | | -3x-1=21 | | 0.75-12=0.50-6 | | B+4=3 | | 42x+21=90 | | 3m(2m+3)=0 | | 0.75+n=2 | | -8t^2+4t+12=0 | | ln(x)-ln(13)=0 | | -65/50 | | -3x+-1+-2=-9 | | 7x-4=5x-46 | | 50y/50 | | 108-1-4y=0 | | 50/50y= | | 2.48/4=x | | 9x+4-2x-2=16 | | .4x-(x+.3333333333)=.06666666666(x+1) | | 4(f+3)=17+4f | | -13b+b=31 | | 15x-35+-8x-36=43 | | x^3-250=0 | | 5(10^3)/15(10^2) | | w+5z=-3 | | 8y+168=7x | | x^3-6x^2+9x-8=0 | | 5-3x=x+5-4x | | 7f-f+3g+15= | | 13.5/1.5 | | 1-n-3n=-15 | | 6x+7(x-7)=16 | | 8y+168=x |